Ibn Al-'Arabi's enduring contribution to Islamic spirituality - Bennett, Donald G. (Kulliyyah of Islamic Revealed Knowledge and Human Sciences, International Islamic University Malaysia, 2017)
This study looks at evidence that Muhyiddin Ibn al-'Arabi left us with a broad outline of his teachings as a spiritual psychology, even if that outline was not perfectly explicit. Evidence is gathered here around a threefold rubric – of key sayings (maxims and frequent re-iterations) which simultaneously highlight rules, development and essential qualities, at the personal level, while engaging psychically with the heart, soul, spirit and mind – to show that Ibn al-'Arabi's teachings were indeed a spiritual psychology, a salient fact that many accomplished and influential scholars through history grasped, especially Haydar 'Amuli of Persia and 'Ali al-Jamal of the Maghrib. There is, in effect, a huge gap being filled by this thesis, in that broad summaries that exist are very inaccurate or full of distortions and rambling attacks, if not simply romantic appreciation, on the one hand, and encyclopedic literalism, on the other. No doubt, useful introductions by clearer-headed scholars exist, but the big picture of the said teachings is not grasped or expounded upon in any clear, systemic way. The benefit of this current outline is to enable a re-opening of Ibn al-'Arabi studies to general audiences or non-experts, both Muslim and non-Muslim, and moreover to move Ibn al-'Arabi from the margins of Islamic tradition to the mainstream of scholarly discourse, research and argumentation as regards spiritual psychology. The task or effort here is simplified by independent and dependent variables within Ibn al-'Arabi's teachings which are easily isolated by virtue of their being re-iterated or used repeatedly, with the assistance of an inductive methodology, inasmuch as Ibn al-'Arabi's dependent variables are more evident, explicit and obvious. The picture of the teaching tradition which emerges is three-fold: written tradition, oral tradition and a tradition clairvoyant sharing. These parallel threads confirm with abundant evidence that Ibn al-'Arabi had a systematic methodology, not random ideas or contradictory inspirations. The most important discovery for future researchers is that Mulla Sadra's explanation of Ibn al-'Arabi's core content in al-Hikmat al-Muta'aliyah is found to be too narrow while Hamza Yusuf's close parallels of Ibn al-'Arabi's content in Purification of the Soul are found to contradict Ibn al-'Arabi's in terms of methodology or approach; hence the uniqueness of this thesis.